2012
DOI: 10.1631/jzus.b1100063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the duration of expressions on the recognition of microexpressions

Abstract: Abstract:Objective: The purpose of this study was to investigate the effects of the duration of expressions on the recognition of microexpressions, which are closely related to deception. Methods: In two experiments, participants were briefly (from 20 to 300 ms) shown one of six basic expressions and then were asked to identify the expression. Results: The results showed that the participants' performance in recognition of microexpressions increased with the duration of the expressions, reaching a turning poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 33 publications
2
92
0
Order By: Relevance
“…The second influential paper is by Shen et al (Shen et al, 2012), which tested two experimental methodologies they called the BART (Brief Affect Recognition Test) condition and the METT (Microexpression Training Tool) paradigm, based on Ekman's work (Ekman & Friesen, 1974) and (Ekman, 2002). The BART condition consisted of showing the six universal expressions after a fixation point (BART), and in the METT paradigm the universal expressions are exhibited between two neutral face sequences.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The second influential paper is by Shen et al (Shen et al, 2012), which tested two experimental methodologies they called the BART (Brief Affect Recognition Test) condition and the METT (Microexpression Training Tool) paradigm, based on Ekman's work (Ekman & Friesen, 1974) and (Ekman, 2002). The BART condition consisted of showing the six universal expressions after a fixation point (BART), and in the METT paradigm the universal expressions are exhibited between two neutral face sequences.…”
Section: Related Workmentioning
confidence: 99%
“…For both experiments, the participants had to say which emotion they perceived. In (Shen et al, 2012), they tried different ranges of expression exhibition times (from 40ms to 300ms) using BART and METT and investigated the possible upper limit to microexpression duration. They concluded that above 160ms identification accuracy begins to stabilize, indicating an upper limit to the microexpressions (i.e., differentiating them from the macroexpressions).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations